Linear and non-linear perturbations in dark energy models - Amendola, Luca (Arxiv, 2003)
I review the linear and second-order perturbation theory in dark energy models with explicit interaction to matter in view of applications to N-body simulations and non-linear phenomena. Several new or generalized results are obtained: the general equations for the linear perturbation growth; an analytical expression for the bias induced by a species-dependent interaction; the Yukawa correction to the gravitational potential due to dark energy interaction; the second-order perturbation equations in coupled dark energy and their Newtonian limit. I also show that a density-dependent effective dark energy mass arises if the dark energy coupling is varying.
Gesehen am 17.11.2017